ANALYSIS OF PUBLIC PERCEPTION TOWARDS UNSUSTAINABLE HOUSING LIVING IN PANTON REU DISTRICT, WEST ACEH REGENCY - Reyza; Anwar; Kasih (RADJA PUBLIKA, 2026)
This study aims to determine public perceptions of uninhabitable housing in Panton Reu District, West Aceh Regency. The research problem is: